2007
DOI: 10.4049/jimmunol.178.2.851
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Adhesion Molecule-1 Expression Is Required on Multiple Cell Types for the Development of Experimental Autoimmune Encephalomyelitis

Abstract: Many members of the Ig superfamily of adhesion molecules, such as ICAM-1 and VCAM-1, have been implicated in the pathogenesis of multiple sclerosis. Although it is well-established that VCAM-1/VLA-4 interactions can play important roles in mediating CNS inflammatory events in multiple sclerosis patients and during the development of experimental allergic encephalomyelitis (EAE), the contributions of ICAM-1 are poorly understood. This is due in large part to conflicting results from Ab inhibition studies and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
108
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 125 publications
(121 citation statements)
references
References 53 publications
10
108
3
Order By: Relevance
“…Given the overlapping functions of Mac-1 and p150/95, deletion of both receptors may result in a complete inhibition of disease similar to that seen when their common ligand intercellular adhesion molecule-1 is deleted. 59 Thus, the ␤2-integrin family members, including p150/95, may offer new therapeutic approaches for demyelinating disease.…”
Section: Discussionmentioning
confidence: 99%
“…Given the overlapping functions of Mac-1 and p150/95, deletion of both receptors may result in a complete inhibition of disease similar to that seen when their common ligand intercellular adhesion molecule-1 is deleted. 59 Thus, the ␤2-integrin family members, including p150/95, may offer new therapeutic approaches for demyelinating disease.…”
Section: Discussionmentioning
confidence: 99%
“…P14 TCR transgenic mice were bred in house. ICAM-1 −/− C57BL/6 mice (Icam1 tm1Alb ) have been described (16,17). CD2-ICAM-1/ICAM-1 −/− transgenic mice were generated as follows.…”
Section: Methodsmentioning
confidence: 99%
“…Several previous studies have harnessed ICAM-1-deficient mice with targeted deletions in exons 4 and 5, in which soluble or membrane-bound splice variants, respectively, may still be expressed (13)(14)(15), thus potentially complicating their interpretation. In the current report, we have used ICAM-1 −/− (Icam1 tm1A1b ) mice, in which the entire coding region of the ICAM1 gene has been deleted (16,17), as well as experimental systems in which ICAM-1 expression is restricted to specific cell types. Rather than a mandatory role for ICAM-1 in the development of CD8 T-cell memory, as suggested by peptide priming studies (3), we detect equivalent or enhanced generation and maintenance of memory-phenotype (CD127 hi , KLRG-1 lo ) CD8 T cells following acute lymphocytic choriomeningitis virus (LCMV) infection of ICAM-1 −/− mice.…”
mentioning
confidence: 99%
“…Adhesion molecules play an important role in the migration of immune cells into the CNS. Patients with MS have increased serum levels of soluble ICAM-1 (sICAM-1), 36,37 and recent studies 9,38 have shown that ICAM-1 is more important than other adhesion molecules in promoting pathological cell infiltration into the CNS and the development of EAE. To determine whether this molecule is involved in the EGCGinduced reduction of inflammatory infiltration, we measured the plasma sICAM-1 level and found that it was lower in mice fed EGCG compared with those fed the control diet ( Figure 9A).…”
Section: Egcg Reduces Circulating Icam-1 and Downregulates Ccr6 Exprementioning
confidence: 99%